Adherence to diabetes risk reduction diet and the risk of head and neck cancer: a prospective study of 101,755 American adults - Wu, Xia; Peng, Linglong; Luo, Haoyun; Xu, Zhiquan; Wang, Jijian; Gu, Haitao; Wang, Yaxu; Xiao, Yi; Zhang, Chaohua; Xiang, Ling (Frontiers in Nutrition, 2023)
Background Adherence to the diabetes risk reduction diet (DRRD) may potentially reduce the risk of developing head and neck cancer (HNC) as the diet includes fruits and limits red and processed meats, known risk factors for HNC. However, there is currently no epidemiological research to investigate this potential association. Methods The present study utilized data on demographics, lifestyles, medications, and diets of participants from the Prostate, Lung, Colorectal, and Ovarian (PLCO) Cancer Screening Trial to explore the potential association between adherence to DRRD and the risk of HNC. We used a DRRD score to evaluate adherence to the dietary pattern and employed Cox regression analysis to calculate hazard ratios (HRs) and 95% confidence intervals (CIs) for HNC risk. Several subgroup analyses were carried out to identify potential effect modifiers, and multiple sensitivity analyses were performed to evaluate the stability of the correlation. The nine components of the DRRD was assessed separately for its association with the risk of HNC. Results During a mean follow up of 8.84 years, 279 cases of HNC were observed. DDRD score was found to be inversely associated with the risk of HNC (HR Q4 vs. Q1: 0.582; 95% CI: 0.396, 0.856; p = 0.005 for trend) in a linear dose–response manner (p = 0.211 for non-linearity). Subgroup analysis indicated this inverse correlation was more pronounced among participants who had never smoked (HRQ4 vs. Q1: 0.193; 95% CI: 0.073, 0.511; p < 0.001 for trend) compared to current or former smokers (p = 0.044 for interaction). The primary association of DDRD and HNC risk remained robust after several sensitivity analyses. Regarding the individual components of DRRD, an inverse association was also observed between the risk of HNC and increased intake of cereal fiber and whole fruit (all p < 0.05 for trend). Conclusion Our findings provide evidence that following the DRRD pattern may reduce the risk of NHC, especially for non-smokers.